Role of Households’ Wealth and Maternal Education in Early Child Development: A Case Study of Punjab, Pakistan - Mujaddad , Hafiz Ghulam; Ashraf, Wajeeha; Danish, Muhammad Hassan (Journal of Development Policy Research and Practice (JoDPRP), 2024)
Children under the age of five are exposed to several hazards in developing countries, such as poverty, inadequate housing, and unstimulating home environments, which have an adverse influence on their cognitive and socio-emotional development. Since learning during adulthood is influenced by earlier developmental stages, these formative years are crucial in shaping a successful adult life. Therefore, the study intends to investigate what causes some children to perform worse than other children of the same age. It utilises data from the Multiple Indicator Cluster Survey (MICS) 2017-18 of 4,043 children from Punjab, Pakistan. Binary Logistic Regression was used for analysis and it demonstrated a positive relationship between early child development, wealth, maternal education, and home stimulating activities with all three measures of child development which include child identification of alphabets, reading at least four popular words, and recognition of numbers or shapes. The result of the study suggests that it is an urgent need of the hour to focus to women’s education and take steps to mitigate poverty in order to enable parents to provide their children with a better learning environment. JEL Classification Codes: I250, H75, P36, J13.